2012
DOI: 10.4081/gi.2012.e13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of leukocyte esterase reagent strip test to detect spontaneous bacterial peritonitis in cirrhotic patients

Abstract: Spontaneous bacterial peritonitis (SBP) is a frequent and sever complication of cirrhotic patients with ascites. The aim of this study was to assess diagnostic value of leukocyte esterase reagent strip test (Medi-Test Combi) for the rapid diagnosis of SBP in cirrhotic patients with ascites in the University Hospital of Imam Reza in Tabriz, Iran. In this study, 132 consecutive samples from cirrhotic patients who underwent abdominal paracentesis were evaluated. These samples were tested by 3 methods: i) manual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our results were superior to this study for utilization of LE strips in rapid diagnosis of SBP this may be attributed to the type of reagent strip we used with lower grade scale (4 grades). Bafandeh has evaluated the diagnostic value of LE reagent strips on 132 patient with cirrhosis and ascites using (Medi-Test combi, France) and the results showed that sensitivity, specificity, PPV and NPV of leukocyte esterase reagent strip test were 97.5%, 84.6%, 74% & 98.7% respectively (5) . Our results were slightly similar according to sensitivity and NPV and superior according to specificity and PPV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were superior to this study for utilization of LE strips in rapid diagnosis of SBP this may be attributed to the type of reagent strip we used with lower grade scale (4 grades). Bafandeh has evaluated the diagnostic value of LE reagent strips on 132 patient with cirrhosis and ascites using (Medi-Test combi, France) and the results showed that sensitivity, specificity, PPV and NPV of leukocyte esterase reagent strip test were 97.5%, 84.6%, 74% & 98.7% respectively (5) . Our results were slightly similar according to sensitivity and NPV and superior according to specificity and PPV.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the mortality from SBP, this test will help to improve the management of SBP. It has been proposed that reagent strip testing for leukocyte esterase is rapid and could be utilized to reduce the time between performing paracentesis and obtaining a presumptive diagnosis of SBP from a few hours to a few seconds (5) . Moreover, such strips would be available everywhere, are easy to use, do not require expertise, thereby allowing antibiotic therapy to be immediately started (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Point of care examination of the ascitic fluid by urinary dipstick was studied extensively by some investigators, but their focus was mainly maintained on detecting infections (namely, spontaneous bacterial peritonitis [SBP]) rather than differentiating between high and low values of SAAG (8)(9)(10)(11). Some studies found acceptable accuracy for dipstick tests (leukocyte esterase) to detect peritonitis in ascitic fluid (12,13), whereas other studies (including the largest one) concluded that dipstick test does not have sufficient sensitivity to detect SBP (14,15). The focus of previous studies on dipstick tests for ascetic fluid was perhaps due to the fact that a rapid diagnosis of SBP would be useful in initiating a suitable empirical antibiotic awaiting the results of culture.…”
Section: Introductionmentioning
confidence: 99%